Chromosome sorting in tetraploid wheat and its potential for genome analysis - Kubaláková, Marie; Kovárová, Pavlína; Suchánková, Pavla; Cíhalíková, Jarmila; Bartos, Jan; Lucretti, Sergio; Watanabe, Nobuyoshi; Kianian, Shahryar F; Dolezel, Jaroslav (Genetics, 2005)
This study evaluates the potential of flow cytometry for chromosome sorting in durum wheat (Triticum turgidum Desf. var. durum, 2n = 4x = 28). Histograms of fluorescence intensity (flow karyotypes) obtained after the analysis of DAPI-stained chromosomes consisted of three peaks. Of these, one represented chromosome 3B, a small peak corresponded to chromosomes 1A and 6A, and a large peak represented the remaining 11 chromosomes. Chromosomes sorted onto microscope slides were identified after fluorescence in situ hybridization (FISH) with probes for GAA microsatellite, pSc119.2, and Afa repeats. Genomic distribution of these sequences was determined for the first time in durum wheat and a molecular karyotype has been developed for this crop. Flow karyotyping in double-ditelosomic lines of durum wheat revealed that the lines facilitated sorting of any arm of the wheat A- and B-genome chromosomes. Compared to hexaploid wheat, flow karyotype of durum wheat is less complex. This property results in better discrimination of telosomes and high purities in sorted fractions, ranging from 90 to 98%. We have demonstrated that large insert libraries can be created from DNA purified using flow cytometry. This study considerably expands the potential of flow cytogenetics for use in wheat genomics and opens the possibility of sequencing the genome of this important crop one chromosome arm at a time.
Keywords: Chromosomes; DNA, Plant; Chromosomes, Plant; Cell Cycle; Metaphase; Physical Chromosome Mapping; In Situ Hybridization, Fluorescence; Microsatellite Repeats; genetické techniky; genom; separace buněk; pšenice; Genome; Genome, Plant; DNA; metafáze; Ploidies; ploidie; Flow Cytometry; hybridizace in situ fluorescenční; modely genetické; Chromosome Mapping; chromozomy; Cell Separation; DNA rostlinná; mikrosatelitní repetice; karyotypizace; Triticum; průtoková cytometrie; Models, Genetic; mapování chromozomů; chromozomy rostlin; Genetic Techniques; genom rostlinný; buněčný cyklus; Karyotyping; fyzikální mapování chromozomů